Cognitive‐behavioral therapy for bulimia nervosa and atypical bulimic nervosa: Effectiveness in clinical settings. Issue 1 (2nd September 2013) - Waller, Glenn; Gray, Emma; Hinrichsen, Hendrik; Mountford, Victoria; Lawson, Rachel; Patient, Eloise
ABSTRACT Objective The efficacy of cognitive‐behavioral therapy (CBT) for bulimic disorders has been established in research trials. This study examined whether that efficacy can be translated into effectiveness in routine clinical practice. Method Seventy‐eight adult women with bulimic disorders (bulimia nervosa and atypical bulimia nervosa) undertook individual CBT, with few exclusion criteria and a treatment protocol based on evidence‐based approaches, utilizing individualized formulations. Patients completed measures of eating behaviors, eating attitudes, and depression pre‐ and post‐treatment. Eight patients dropped out. The mean number of sessions attended was 19.2. Results No pretreatment features predicted drop‐out. Treatment outcome was similar whether using treatment completer or intent to treat analyses. Approximately 50% of patients were in remission by the end of treatment. There were significant improvements in mood, eating attitudes, and eating behaviors. Reductions in bingeing and vomiting were comparable to efficacy trials. Discussion The improvements in this "real‐world" trial of CBT for adults with bulimic disorders mirrored those from large, funded research trials, though the conclusions that can be reached are inevitably limited by the nature of the trial (e.g., lack of control group and therapy validation). © 2013 Wiley Periodicals, Inc. (Int J Eat Disord 2014; 47:13–17)